Drought Stress Signal Promote the Synthesis of more Reduced Phenolic Compounds (Chloroform Insoluble Fraction) in Tridax procumbens - Gnanasekaran, Natesan; Kalavathy, Subramanian (Free Radicals and Antioxidants)
Background: Plant’s are ability to manage with abiotic stress factors are mainly altered the metabolic pathways and produces a varied range of secondary metabolites. Secondary metabolite manufacture is a serious part of the defense response in stress circumstances. Objectives: The study was aim to find out the impact of drought stress factor on in vitro antioxidant potential of chloroform insoluble fraction (phenolics) of leaves and flowers extract of Tridax procumbens. Materials and Methods: The matured leaves and flowers of Tridax were collected widely from the four different locations;- Hilly dry-terrain; Hilly wet-terrain; Low dry–land; Low wet-land. The collected leaves and flowers of Tridax were washed with distilled water, shade dried, coarsely powdered and extracted using 70% ethanol and fractionated by chloroform to obtained chloroform insoluble fractions. The chloroform insoluble fraction then subjected into various in vitro free radical scavenging activities. Results: The drought stress significantly increased the sucrose content in the leaves, chloroform insoluble fractions (water soluble), total phenolics and decreased relative leaf water contents and chloroform soluble fractions when compared with well water state of Tridax. The in vitro free radical scavenging activities results revealed that drought had constructive effects on radical scavenging and antioxidant capacity. Conclusion: In dry land of the Tridax procumbens (both hilly dry-terrain and low dry-land) induced drought stress-related metabolic alterations and free radical production. In this condition Tridax need oversupply of reduced phenolics for tolerance and prevent the oxidative damage of the cells. As a result the metabolic processes are shifted towards biosynthesis of highly reduced phenolics in the Tridax for better adaptation.
Keywords: Drought stress; Tridax procumbens; Chloroform Insoluble fractions; In vitro antioxidant